kanker servik Praktik Pencegahan Skrinning Kanker Servik di kalangan Petugas Kesehatan : Literature Review - Fitriani, Desi; Huda, Nurul; Wahyuni, Sri (MEDIA ILMU KESEHATAN, 2024)
Background: Early diagnosis and screening being vital in preventing related deaths with servical cancer. Despite its importance, screening coverage in developing countries remains low. Healthcare workers play a key role in increasing coverage by educating and motivating the public. However, limited knowledge about cervical cancer screening hinders their practices.Objective: Explores cervical cancer screening practices among healthcare workers.Methods: A literature review was conducted using PubMed, ScienceDirect, and Google Scholar, identifying 2,163 articles. After filtering and applying inclusion criteria, 12 articles were selected. Inclusion criteria: 1) original research (2019-2024), 2) focuses on cervical cancer screening practices, 3) healthcare workers as subjects. Exclusion criteria: 1) studies not related to healthcare workers, 2) theses, reviews, abstracts, or proceedings.Results: Findings reveal that cervical cancer screening practices among healthcare workers are low, influenced by insufficient knowledge and negative attitudes. Knowledge is enhanced through training and active participation in screening activities. Regional demographic factors also impact healthcare workers' involvement in screening promotion.Conclusion: Training programs are critical to improving healthcare workers' knowledge and attitudes towards cervical cancer screening. Policymakers should implement robust monitoring and evaluation programs to sustain these efforts.